セッピョウ コア ノ ショリ ホウホウ ノ カイリョウ - 神山, 孝吉; カミヤマ, コウキチ; 飯塚, 芳徳; イイズカ, ヨシノリ; Kamiyama, Kokichi; Iizuka, Yoshinori; Stauffer, Bernhard (2001)
P(論文) 雪氷コアの解析には, 初期に様々な処理作業を必要とする。特に化学解析の場合には試料を解析機器に導入する前の処理作業が不可欠であり汚染除去の方法など従来から検討されてきた。ここでは低温実験室で行っていた作業の一部を常温実験室で行い, 処理作業環境の向上を目指した。極地研究所の低温実験室に冷凍保管していた雪氷コアの切断作業を常温実験室に設置した温度コントロールチェンバーを利用して行った。チェンバー内部に小型のコア切断機器を設置し試料を整形した後, 直ちにコア密度を測定した。融解後試料の電気伝導度などを測定し, ラベルを記載した専用容器に保管し, その後トリチウム濃度などの計測に供した。コア試料の切断・密度測定・融解・電気伝導度測定・融解保存容器への保管整理で5m/6時間/一人の作業量効率であることを確認した。また冷凍状態での雪氷コア試料を, 常温実験室で深さ方向の連続融解と試料のサンプル容器への自動分注方法について検討した。実際のコア試料を連続融解しイオン分析用に専用の容器への分注を行ったが, 10試料/15cm/30分/一人の作業量を必要とした。なお作業については複数の人間が携わる必要はなく処理作業効率が上昇し, 測定結果は十分満足できる精度であった。 Ice core analyses start with the processing of ice cores. Especially for chemical analyses, pre-treatments for introducing the samples to the measuring instruments without contamination is essential. Part of processing can be carried out under a normal laboratory instead of the cold one to improve the efficiency of processing the core samples. The ice core cutting was carried out in a small chamber, with temperature control, installed in a normal laboratory. The ice core sample was cut with a small instrument in the chamber and melted after the determination of solid bulk density. The melted samples were stored after labeling for the planned measurements, such as HTO measurements. The core processing including cutting in the chamber, measurement of bulk density and electrical conductivity before the storage of melted samples with labeling, were carried out at the rate of 5m/(6 hours・person). The continuous melting and sampling procedures for the ice core sample toward the depth direction are also discussed. Continuous melting with continuous sampling for measurement of ion chromatography was carried out on 10 samples/(15cm・30min・person). The processing was efficient for the delicate sampling, and the data obtained in the procedure was supported by those obtained with normal procedure. departmental bulletin paper